Controlled synthesis of Co2P particles with various morphologies using an in-situ melt reaction. (15th January 2016) - Zuo, Min; Pan, Luyao; Sun, Teng; Zhao, Degang; Wang, Zhenqing; Geng, Haoran
Abstract: In this article, a new type of Cu–Co–P alloy with different atomic ratios of Co/P has been successfully synthesized, in which the Co2 P particles have been formed. By means of the melt-spinning and phase extraction technologies, the pure Co2 P particles with various morphologies could be obtained. It has been found that with the atomic ratio of Co/P changing from 1:2, 1:1, 3:2 to 2:1, the Co2 P particles exhibit the morphologies of hollow hexagonal and quadrangular prisms, short rod-shape, fine and near-spheroidal particles, fibers and spheres, respectively. Besides of the stoichiometry of reactants Co/P, the non-equilibrium solidification caused by melt-spinning might be another reason for the morphological evolution of the Co2 P phase. The synthesis of Co2 P particles by the in-situ melt reaction provides an efficient, stable, controllable and green environment-friendly preparation method, in which the Cu–P alloy is supplied as the phosphorus resource. Meanwhile, this discovery provides new opportunities for the synthesis of transition metal phosphides. Graphical abstract: Highlights: A new type of Cu–Co–P alloys with different atomic ratio of Co/P has been successfully synthesized. Pure Co2 P particles with various morphologies could be obtained by an in-situ melt reaction. The stoichiometry of Co/P and non-equilibrium solidification might be the reasons for the morphological evolution of Co2 P. This discovery provides new opportunities for the synthesis of transition metal phosphides.